Knowledge and Attitudes amongst Medical Students on Health Research and Scientific Publications - Mahanta Putul; Kinkar Mahanta; Kalim Ullah; Deka Subha Jyoti; Dutta Bhaskar Jyoti (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Most of the medical colleges, in general, have been suffering from lack of health researchand scientific publications among the students in particulars and faculties in general. Health research andscientific publications are important medical students’ activity for healthy and prosperous medical education.Objective: This study assesses the level of knowledge and attitudes regarding health research and scientificpublications among medical students. Methodology: It is a cross-sectional descriptive study conductedamong 100 medical students and were randomly picked up at Assam Medical College and Hospital in theyear 2019. A prefix pretested proforma was used to determine the knowledge and attitudes of the students.Informed consent was taken. The data thus obtained was analyzed using MS Excel. Results: A total of25(25%) students feel confident in interpreting and writing a research paper, while 39(39%) says they cando it with seniors’ support.In comparison, 20(20%) says no it saying their incapabilities of doing it. Majority 70(70%) students saythat they have not participated in a research project (apart from mandatory academic projects) and 90(90%)says that they were never written any scientific paper. A good number of 80(80%) students feel that lack ofa mentor is the cause of no publication while 60(60%) students believe that undergraduate students can planand conduct a research project and write a scientific paper. Lack of facilities for doing research is acceptedby 50(50%) of students to be another cause of no research and publication while 40(40%) receive lack offunding to be the root cause of no study. Conclusion: With the limited resources of this study, our findingshave highlighted a low to moderate level of knowledge of undergraduate medical students in researchmethodology principles and the critical impact of research methodology workshops. These findings can beutilized for future health research planning to improve the situation in India’s field of medical education.